The validity of the confirmation administered outside of the church: Canon 844 - Vere, Peter J. (CLSA advisory opinions, 2001-2005, 2001)
According to Catholic jurisprudence, is the sacrament of confirmation, when administered by a so-called Traditionalist bishop of Archbishop Thuc's lineage, valid? According to Catholic jurisprudence, is the same sacrament valid when administered by a cleric of so-called Old Catholic or Old Orthodox lineage in North America?